Plastyczne Skręcanie Prętów Kołowo-Zakrzywionych o Dowolnej Niejednorodności Poprzecznej - Galos, M.; Życzkowski, M. (Engineering Transactions, 1970)
Consideration is given in this paper to the problem of the plastic twisting of ciruclarly curved rods, made of material having an arbitrary transverse inhomogeneity. To that end, use is made of the established mathematical analogy which occurs between that problem and the problem of plastic twisting of prismatic rods with arbitrary transverse inhomogeneity. For the solution, the stress function h is used, which enables presentation of the methods serving for the effective calculation of the limiting load of the twisted rods. The paper is illustrated with examples.